The lost Americans : a novel - Bollen, Christopher, 1975- (Harper, an imprint of HarperCollinsPublishers, 2023)
A young woman finds herself in the crosshairs of powerful and very dangerous enemies when she travels to Cairo to uncover the truth about her brother's mysterious death.